Financial development, trade openness and economic growth in MENA countries: TYDL panel causality approach - Hicham AYAD; Mostéfa BELMOKADDEM (Theoretical and Applied Economics, 2017)

(untitled)
This paper examines the causal relationship between financial development (measured as Kaopen index and Line and Milesi-Ferreti index), trade openness and economic growth for 16 MENA countries within the panel co-integration techniques, panel VAR model and TYDL (Toda, Yamamoto, Dolado and Lutkepohl) Granger causality (1996), the empirical results show that both of finance-led growth and trade-led growth hypothesis seem to be rejected for the group as a whole. The results imply that financial development and trade liberalization do not seem to have made a significant impulse on economic growth for the period 1980-2014.